Nea Paphos as a center of pottery production in the Hellenistic period: the contribution of Polish research in Maloutena and the Agora - Ewdoksia Papuci-Władyka (Polish Archaeology in the Mediterranean)
The issue of the existence of local ceramics production in the ancient city of Nea Paphos in the Hellenistic period has been a subject of scientific discussion since the 1980s. The first programs for archaeometric analysis of ceramic samples were also implemented at that time, but unfortunately, for various reasons, they were discontinued. The program of archaeometric analyses was resumed on a large scale as part of the Paphos Agora Project and other Polish research initiatives implemented in Paphos. Samples of various categories of ceramics, analyzed at the Fitch Laboratory of the British School at Athens, were taken both from material collected during the research of the University of Warsaw conducted since 1965 in the area of Maloutena (i.a. Villa of Theseus, House of Aion, “Hellenistic” House), as well as from finds from excavations conducted by the Jagiellonian University in Kraków since 2011 in the Agora. The article discusses the prerequisites for the existence of ceramic production in Paphos and the surrounding area and summarizes the results of macroscopic, physio-chemical, and petrographic analyses, which confirm the local production of ceramics in Paphos and the surrounding area in the Hellenistic period. The produced categories of pottery are briefly presented.